In-between space and social interaction: a case study of three neighbourhoods in Izmir - Can, Işın (2012)
This research discusses the intermediate space that lies between private and public space, as well as its definition and importance in space configuration regarding urban morphology and social relations. It investigates how the organisation of in-between space affects social interaction in different urban patterns. As many researchers caution, terms such as semi-private and semi-public can be deceptive in attempting to define the relationship between the building and the street, because of the overlapping territory of this space. Therefore in this study the in-between space concept is used to portray this space and the interrelations that take place.